Experience of the use of hirudotherapy in the complex therapy of dizziness - Yu. N. Neryanova; L. V. Kuzmenko (Zaporožskij Medicinskij Žurnal)
Dizziness is sufficiently widespreaded. Course hirudotherapy was included in the complex treatment 52 patients. It was found that leeching significantly improves health of patients, which is manifested as a reduction in dizziness, ataxia, disappearance of symptoms of fever, cold. Also normalization of blood pressure, reduce pain in the neck, headaches, improve sleep were seen.